IMPLEMENTASI AREA TRAFFIC CONTROL SYSTEM (ATCS) SEBAGAI PELAYANAN PUBLIK DI DINAS PERHUBUNGAN KOTA MALANG - Agies Nina Pramestarivia; Iradhat Taqwa Sahidi (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2022)
The growth of cities and the movement of people who have experienced very rapid development is aimed at an increasing population, increasing income and increasing workforce. This raises the demand for transportation to increase so that it requires solutions to meet the conditions that occur in safe and orderly traffic. One form of solution in improving services on the transportation system is the presence of ATCS. The purpose of this study is to determine the implementation of the Area Traffic Control System (ATCS) as a public service at the Malang city transportation service. The theory used in this research is the implementation of policies according to George Edward III which there are 4 factors that influence the success or failure of policy implementation. This study used descriptive qualitative method. Data collection was done by means of interviews, observations, and documentation, then the data were analyzed by data collection procedures, data reduction and drawing conclusions. The results of this study indicate that the ATCS solution provided by the Malang City Transportation Service has been running well as evidence that the application of ATCS can reduce the level of accidents and congestion that occurs in traffic.